Work-Related Musculoskeletal Disorders among Plastic Surgeons: A Systematic Review - Epstein, Sherise; Tran, Bao N.; Capone, Avery C.; Ruan, Qing Z.; Lee, Bernard T.; Singhal, Dhruv (Journal of Reconstructive Microsurgery, 2018)
Background To date, no review has been conducted on the growing body of literature describing various work-related musculoskeletal disorders (MSDs), ergonomic hazards, and potential interventions relevant to plastic surgeons. This systematic review sought to (1) define the scope of coverage of this important issue in the peer-reviewed literature; (2) critically assess the evidence; and (3) provide recommendations for future directions.Methods We conducted a literature search of MEDLINE, Embase, Web of Science, and PubMed from the inception of each database until 2016. All articles reporting on work-related MSDs or ergonomics among plastic surgeons were reviewed, summarized, and assessed for trends.Results Sixteen articles met our inclusion criteria including five expert opinions, four cross-sectional studies and case reports/series, one review, and six experimental studies. Four articles presented evidence on disease burden. The most commonly described work-related MSD was cervical spine disease, for which one study reported a career prevalence of 24.7% (point prevalence in the general population: 0.1–0.4%); three studies reported 64 cases of surgeon work-related MSD resulting in surgical intervention, decreased productivity, or involuntary early retirement. Eight studies described interventions, most of which aimed to improve the ergonomics of microsurgery.Conclusion This review found low-level evidence of plastic surgeons' vulnerability to a work-related MSD at times severe enough to end careers. Further investigation is needed to clearly define this important problem in plastic surgery. Specifically, future directions should include more methodologically rigorous epidemiologic studies evaluating disease burden.
Keywords: work-related musculoskeletal disorder; occupational injury; ergonomics; surgical ergonomics; safety; work safety; disability; plastic surgery; microsurgery